Using Information Technologies In Studying Professionally Oriented English (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
This article investigates the role of information technologies in studying professionally oriented English and analyzes how digital tools improve students’ language competence, professional vocabulary, communicative skills, and independent learning abilities. The study is based on qualitative observation, analysis of teaching practices, and review of relevant scholarly literature
Keywords: professionally oriented English; information technologies; ESP; digital learning